2022
DOI: 10.22541/au.165777854.44197862/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A key evolution in gene expression plasticity for freshwater colonisation in early life stage of fish

Abstract: Colonisation of freshwater habitats by marine animals is a remarkable evolutionary event that has enriched biodiversity in freshwater ecosystems. For successful freshwater colonisation, high physiological plasticity is presumed to be necessary, but its evolutionary basis has not been detailed. Marine-originated amphidromous species, which regularly migrate between freshwater and marine environments, have repeatedly lost migratory behaviour in many lineages, which sometimes triggered species radiation in freshw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Among the three amphidromous species, only G. urotaenia contains several FWR populations in lakes and streams, whereas the others spend their larval periods in the sea (Umino et al, 2015;Oto et al, 2022). A previous study demonstrated the relative superiority of the osmoregulatory performance of G. urotaenia larvae under freshwater conditions (Oto et al, 2022). However, this may not be sufficient to fully explain the life-history variations among Gymnogobius species because of some osmoregulatory flexibility also in the other two species.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Among the three amphidromous species, only G. urotaenia contains several FWR populations in lakes and streams, whereas the others spend their larval periods in the sea (Umino et al, 2015;Oto et al, 2022). A previous study demonstrated the relative superiority of the osmoregulatory performance of G. urotaenia larvae under freshwater conditions (Oto et al, 2022). However, this may not be sufficient to fully explain the life-history variations among Gymnogobius species because of some osmoregulatory flexibility also in the other two species.…”
Section: Introductionmentioning
confidence: 91%
“…All three species usually spawn in freshwater stream areas, migrate downstream to the sea immediately after birth, drift along the coast for 2-3 months during the larval stage, and return to streams when juveniles, forming large schools (Dotu, 1955;Harada, 2002). However, only G. urotaenia has established freshwater resident (FWR) populations in lakes and streams in several regions (Umino et al, 2015;Oto et al, 2022). No FWR populations have been reported for G. petschiliensis or G. opperiens.…”
Section: Target Species and Samplingmentioning
confidence: 99%
See 3 more Smart Citations